Promoting Effective Schooling through Education Decentralization in Bangladesh, Indonesia, and Philippines - Jere R. Behrman; Anil B. Deolalikar; Lee-Ying Soon (Asian Development Bank (ADB), 2002)
"Among developing member countries (DMCs), Indonesia and the Philippines rank fairly high in the distribution of real GDP per capita in PPP dollars while Bangladesh ranks much lower. In terms of aggregate schooling, the Philippines has secondary and tertiary enrollment rates that are substantially higher, while Indonesia has rates that are substantially lower, than that predicted based on all DMCs and their respective real products per capita. The Philippines also has expected grades for synthetic cohorts that are substantially above the overall mean for DMCs. In terms of public expenditures on education, all three countries have about the same percentage of GNP invested in education, a little over 2 percent, which is significantly below the level predicted by the experience of all DMCs given their respective real products per capita. There has been considerable public pressure for decentralization of education in DMCs in recent years. This pressure has been driven largely by fiscal constraints but has also been motivated by concerns over the effectiveness of a centralized system for delivering education services. The three country studies provide a rich characterization of the evolving - and in certain respects, rapidly changing - education systems in these DMCs."
hdl:11540/2061
Keywords: 330; Bildungspolitik; Bildungsinvestition; Dezentralisierung; Bangladesch; Indonesien; Philippinen